2010
DOI: 10.1176/appi.ajp.2010.09121743
|View full text |Cite
|
Sign up to set email alerts
|

“A Disease Like Any Other”? A Decade of Change in Public Reactions to Schizophrenia, Depression, and Alcohol Dependence

Abstract: Objective Clinicians, advocates, and policy makers have presented mental illnesses as medical diseases in efforts to overcome low service use, poor adherence rates, and stigma. The authors examined the impact of this approach with a 10-year comparison of public endorsement of treatment and prejudice. Method The authors analyzed responses to vignettes in the mental health modules of the 1996 and 2006 General Social Survey describing individuals meeting DSM-IV criteria for schizophrenia, major depression, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

41
785
6
16

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,021 publications
(869 citation statements)
references
References 43 publications
41
785
6
16
Order By: Relevance
“…As Angermeyer et al (2011) have shown, in a number of OECD countries there has been increased public preparedness to accept biogenetic (including neurobiological) explanations of schizophrenia, depression and alcohol dependence. However, trends in the public's acceptance of neurobiological information are not uniform across mental disorders (Schnittker, 2008;Pescosolido et al, 2010;Easter, 2012;Rüsch et al, 2012). Surveys from North America and the United Kingdom show that whereas over three-quarters of the population will label schizophrenia, bipolar disorder and depression as 'mental illnesses', only one-half are prepared to label alcohol dependence or drug abuse in the same way (Pescosolido et al, 2010;Rüsch et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Angermeyer et al (2011) have shown, in a number of OECD countries there has been increased public preparedness to accept biogenetic (including neurobiological) explanations of schizophrenia, depression and alcohol dependence. However, trends in the public's acceptance of neurobiological information are not uniform across mental disorders (Schnittker, 2008;Pescosolido et al, 2010;Easter, 2012;Rüsch et al, 2012). Surveys from North America and the United Kingdom show that whereas over three-quarters of the population will label schizophrenia, bipolar disorder and depression as 'mental illnesses', only one-half are prepared to label alcohol dependence or drug abuse in the same way (Pescosolido et al, 2010;Rüsch et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, trends in the public's acceptance of neurobiological information are not uniform across mental disorders (Schnittker, 2008;Pescosolido et al, 2010;Easter, 2012;Rüsch et al, 2012). Surveys from North America and the United Kingdom show that whereas over three-quarters of the population will label schizophrenia, bipolar disorder and depression as 'mental illnesses', only one-half are prepared to label alcohol dependence or drug abuse in the same way (Pescosolido et al, 2010;Rüsch et al, 2012). Furthermore, there is incomplete concordance between preparedness to describe conditions as 'mental illnesses' and to accept neurobiological explanations of them (Pescosolido et al, 2010;Rüsch et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This trend has been fueled by changes in funding priorities for mental health research, including President Obama's Brain Research through Advancing Innovative Neurotechnologies initiative (4,5). The public's understanding of mental disorders has also become more biological (6).…”
mentioning
confidence: 99%
“…It was a shift from a biopsychosocial descriptive approach to a medically based research model (Wilson, 1993). As the medical model widened, so did the thinking that the mental disorders were brain disorders or chemical imbalances (Pescosolido et al, 2010).…”
Section: Rethinking the Field: A Radical Approach (Birrell)mentioning
confidence: 99%